Dual-target peripheral and central magnetic stimulation for rehabilitation of chronic pelvic pain syndrome associated with psychosomatic symptoms: Study protocol for a randomized controlled trial - Chunmei Luo; Jiabei He; Degui Chang; Haibo Lan; Meizhu Zhao; Xiaobin Zhen; Ren Liu; Lanjin Bai; Xueqian Li; Siyi Tian; Xiangdong Yang (PLoS ONE, 2025)
Introduction Chronic pelvic pain syndrome (CPPS) is frequently associated with psychological issues. Repetitive peripheral magnetic stimulation (rPMS) is potentially effective in treating CPPS, while repetitive transcranial magnetic stimulation (rTMS) has demonstrated therapeutic effects on anxiety and depression. Therefore, the study proposed herein aims to assess the efficacy and safety of dual-target magnetic stimulation in CPPS patients with psychological disorders. Methods This prospective, double-blind, randomized controlled trial will recruit 75 CPPS participants. After stratification by sex, participants will be randomly assigned via block randomization (1:1:1), sequentially based on enrollment order, to one of three groups: dual-target magnetic stimulation (rPMS and rTMS), rPMS, and sham stimulation, all receiving standard treatment. The dual-site magnetic stimulation group will receive left dorsolateral prefrontal cortex (DLPFC) rTMS (120% resting motor threshold [RMT], 10 Hz, 4-s stimulation, 26-s interval, 3000 pulses in total [depression cases]) or right DLPFC rTMS (120% RMT, 1 Hz, 10-s stimulation, 2-s interval, 1000 pulses in total [anxiety cases]) combined with rPMS (50% of maximum stimulation intensity, 20 Hz, 2-s stimulation, 28-s interval, 1600 pulses in total). The rPMS group will receive only rPMS. The sham stimulation group will undergo sham transcranial and peripheral stimulation. All treatments will be administered five times a week, once daily, for 4 weeks. Primary outcomes will be the pelvic pain scale (females) or the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI, males). Secondary outcomes will include assessment of pelvic floor muscle surface electromyography, pudendal nerve motor evoked potentials, the Depression, Anxiety, and Stress Scale (DASS-21), and the Short Form 36 (SF-36) quality of life scale. Discussion We hypothesize that dual-target magnetic stimulation will show greater effectiveness than rPMS and sham stimulation in relieving pain symptoms and psychological distress in CPPS patients with comorbid mental disorders. Clinical trial registration The study was prospectively registered at the Chinese Clinical Trial Registry (ChiCTR; http://www.chictr.org.cn, ID: ChiCTR2300078761) on December 18, 2023; Protocol version 1.0–20220709.